2019
DOI: 10.1101/772061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The MEK1/2 pathway as a therapeutic target in high-grade serous ovarian carcinoma

Abstract: Rationale: High-grade serous ovarian carcinoma (HGSOC) is the deadliest of gynecological cancers due to high rate of recurrence and acquired chemoresistance. Mutation and activation of the RAS/MAPK pathway has been linked to cancer cell proliferation and therapeutic resistance in numerous cancers. While RAS mutations are not commonly observed in HGSOC, less is known about downstream pathway activation. We therefore sought to investigate the role of MEK1/2 signaling in ovarian cancer.Methods: MEK1/2 pathway act… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, in breast cancer, inhibition of AXL increased CSC chemosensitivity [ 106 ] , whereas histone deacetylase inhibitors manifested preferential targeting of breast CSCs, suggesting a potential therapeutic effect in ovarian CSCs as well [ 107 ] . In addition, a recent study of high-grade serous ovarian cancer revealed that an MEK1/2 inhibitor, trametinib, arrests cell proliferation but also enriches cancer stemness, suggesting a need for a combination regimen with CSC-targeted therapy [ 108 ] .…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Interestingly, in breast cancer, inhibition of AXL increased CSC chemosensitivity [ 106 ] , whereas histone deacetylase inhibitors manifested preferential targeting of breast CSCs, suggesting a potential therapeutic effect in ovarian CSCs as well [ 107 ] . In addition, a recent study of high-grade serous ovarian cancer revealed that an MEK1/2 inhibitor, trametinib, arrests cell proliferation but also enriches cancer stemness, suggesting a need for a combination regimen with CSC-targeted therapy [ 108 ] .…”
Section: Clinical Studiesmentioning
confidence: 99%